إستراتجيات تنفيذ الأوامر المالية في البورصة في ظل التحول نحو المتاجرة عالية التردد (HFT) - سهيلة, بوكي; نعيمة, بادي; محمد, برتيمة (University of eloued جامعة الوادي, 2020)
يعالج هذا البحث موضوع التداول عالي التردد واستراتيجياته والأوامر المالية في ظل المتاجرة عالية التردد, وذلك للإجابة على الاشكالية المتمثلة في إلى أي مدى تطورت استراتيجيات الأوامر المالية في ظل المتاجرة عالية التردد وما تأثير ذلك على آليات عمل الأسواق المالية.؟ بهدف تسليط الضوء على الجوانب النظرية المتعلقة بالأسواق المالية والتطور التكنولوجي للأوامر المالية التي شهدتها البورصات العالمية الكبرى خلال السنوات الأخيرة لتقديم مقترحات وللوصول لهذه الأهداف المسطرة قمنا باستخدام المنهج التاريخي والوصفي و التحليلي حيث اقتضت الضرورة إلى تقسيم البحث إلى ثلاثة فصول يتناول الأول الاطار النظري والفني للأسواق المالية في حين يتناول الثاني الاطار التنظيمي لاستراتيجيات المتاجرة عالية التردد, أما الثالث فتناول آثار الاستراتيجيات على طبيعة عمل الأوامر في الأسواق المالية. وقد توصلنا إلى أن يستخدم المتداولون الاستراتيجيات التعامل و المراجحة لتقديم السيولة أو لنقلها فيما بينهم في الأسواق. وعليه اقترحنا يجب على المتداولين عالي التردد التأكد من أن هذه الخوارزميات تم اختبارها قبل نشرها في الأنظمة الحية للأسواق، قد تتسبب هذه الخوارزميات التي تم إصدارها قبل الأوان في خسائر لكل من المتداولون والبورصات.This Paper deals with the issue of high-frequency trading and its strategies and financial orders in light of high-frequency trading, in order to answer the problematic of to what extent have financial order strategies developed in light of high-frequency trading, and what is the affect of this on the mechanisms of financial markets. In order to shed light on the theoretical aspects related to the financial markets and the technological development of financial orders that the major global stock exchanges have witnessed in recent years to submit proposals and to reach these established goals, we used the historical and descriptive analytical approach, as it was necessary to divide the research into three chapters. The first deals with the theoretical and technical framework of financial markets while it deals with The second is the regulatory framework for high-frequency trading strategies, and the third dealt with the effects of strategies on the nature of the work of orders in the financial markets. We have concluded that traders use trading and arbitrage strategies to provide liquidity or transfer it among themselves in the markets. Therefore, we suggested that high-frequency traders should ensure that these algorithms are tested before Deployed in live market systems, any algorithms released prematurely could cause losses to both traders and exchanges.
مذكرة ماستر اقتصاد نقدي وبنكي
Keywords: التداول عالي التردد ، التداول الخوارزمي، الاستراتيجيات ،الأوامر المالية، صانع السوق.; high-frequency trading, algorithmic trading, strategies, financial orders, market maker.